Analisis Studi Kelayakan Proyek Terhadap Aspek Finansial Perumahan di Kota Palangka Raya - Eddy Surya Risky Fajary; Subrata Aditama K. A. Uda; Dewantoro Dewantoro (Fakultas Teknik, 2022)
The provision of new land for housing development is increasingly widespread in various areas in Palangka Raya, both housing construction by developers, developers working with the government and individuals. This gives a signal that the prospect of life in Palangka Raya has a promising future. PT. Sanur Griya Tama built subsidized housing with a building area of 36 m2 as many as 99 units. To avoid the risk of loss, as this project requires quite high development costs, we first need to conduct a financial feasibility study. The purpose of this study is to analyze the financial viability of the project. Analyze financial viability using investment measure scale with NPV, BCR, IRR and sensitivity. After analysis, it was concluded from a financial point of view that the investment cost was IDR 6.500.000.000,-. Feasibility of the investment over a 28-month period, with a calculated NPV of IDR 3.734.558.414,-, a BCR of 1,236, an IRR of 45%, a sensitivity to price increases of 25%, and a discount rate of 45%. Living in Grand Sanur Griya Tama is a viable and very profitable investment.